2011
DOI: 10.4297/najms.2011.320
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based stress reduction: A non-pharmacological approach for chronic illnesses

Abstract: Background:Mindfulness Based Stress Reduction (MBSR) therapy is a meditation therapy, though originally designed for stress management, it is being used for treating a variety of illnesses such as depression, anxiety, chronic pain, cancer, diabetes mellitus, hypertension, skin and immune disorders.Aim:The aim of this systematic review is to determine the efficacy of MBSR in the treatment of chronic illnesses; it's mechanism of action and adverse effects. It describes an alternative method of treatment for phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 15 publications
3
65
0
3
Order By: Relevance
“…Information on stress management was adapted from principles of Mindfulness Based Stress Reduction (MBSR) [16], a promising mind-body intervention [28–31]. The major techniques included were: being present in the moment, responding and not reacting to stress, awareness of breath meditations (two versions: short 10 min; long 25 min), body scan, mindful eating, and mindful yoga.…”
Section: Methodsmentioning
confidence: 99%
“…Information on stress management was adapted from principles of Mindfulness Based Stress Reduction (MBSR) [16], a promising mind-body intervention [28–31]. The major techniques included were: being present in the moment, responding and not reacting to stress, awareness of breath meditations (two versions: short 10 min; long 25 min), body scan, mindful eating, and mindful yoga.…”
Section: Methodsmentioning
confidence: 99%
“…According to Fairfax [42], mindfulness is being integrated into intervention models such as Mindfulness-based Cognitive Therapy (MBCT) [27,28,43], MBSR [29] and Mindfulness-based Relapse Prevention (MBRP) [25] because of the high success rate in reducing stress and treating other symptoms by using mindfulness-based interventions. According to Vujanovic et al [25], mindfulnessbased therapy lowered anxiety and trauma-related symptoms in patients with PTSD, while Hofmann et al [43] and Niazi [44] reported that mindfulness-based therapy reduced anxiety and depression in patients with mood disorders. These findings were further supported by Tacon et al [23] and Ledesma & Kumano [5] whose studies found that cancer patients became less stressful and less reactive to stress after being exposed to mindfulness-based therapy.…”
Section: Hypothesismentioning
confidence: 99%
“…D'autres travaux vont dans ce sens, c'est-à-dire une meilleure acceptation par les patients de leur pathologie chronique, une amélioration des stratégies d'adaptation à leur situation et un renforcement de leur implication dans les soins, dans leur santé, notamment pour l'acupuncture [20][21][22]. De la même façon, si l'hypnose et la méditation, classées dans les approches psychocorporelles des médecines complémentaires, montrent une certaine efficacité sur le symptôme évalué directement par des études, néanmoins de qualité variable et assez hétérogènes [23][24][25][26][27], leurs actions sur les aspects cognitifs et affectifs de la douleur paraissent supérieures [28]. Certains auteurs proposent d'ailleurs une action en tandem de ces deux approches sur les aspects d'acceptation et de modulation cognitive [29].…”
Section: Quelles Sont Ces Médecines Complémentaires ?unclassified